2017
DOI: 10.4236/oalib.1103683
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of Edible Seed Hemicelluloses

Abstract: In this work, galactomannans and xyloglucans were isolated from the seed endosperm and cotyledon of Brazilian non-conventional sources, respectively. Extraction yields, monosaccharide ratios, macromolecular parameters and molar mass distributions were determined and compared to commercial guar gum and Locust Bean Gum (LBG). The extraction yield in relation to seed mass ranged from 7.0% to 40.63%, with xyloglucan yields being higher than galactomannan yields. Schizolobium parahyba and Caesalpinia pulcherrima ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
0
8
1
Order By: Relevance
“…Hemicelluloses have both structural and storage roles in the analyzed seeds, and is a typical feature of the coffee bean, which has part of its reserve material stored in the walls of endosperm cells.. Hemicelluloses can account for ca. 40-60% of the dry weight of seeds and consist mainly in galactomannans and arabinogalacturonnan proteins (Clifford, 1985;Sousa et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Hemicelluloses have both structural and storage roles in the analyzed seeds, and is a typical feature of the coffee bean, which has part of its reserve material stored in the walls of endosperm cells.. Hemicelluloses can account for ca. 40-60% of the dry weight of seeds and consist mainly in galactomannans and arabinogalacturonnan proteins (Clifford, 1985;Sousa et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Native starch granule is composed of amylose, a linear glucose chain attached by α-1,4 glucosidase bond, and amylopectin, a branched glucose chain with branching at α-1,6 postition [6]. Many studies have shown that the amylose-amylopectin ratio affects the functionality and chemical properties of starch as a biopolymer [8,14].…”
Section: Starch As a Renewable Materials Feedstock For Advanced Applicationsmentioning
confidence: 99%
“…Starch has A, B and C crystal structures, which is a function of its origin. In general, it has a small granule size and comes in various shapes based on the source [6]. The granule is composed of anhydroglucose units linked by α-1,4 glycosidic bonds to form amylose and amylopectin polymer entities.…”
Section: Starch As a Renewable Materials Feedstock For Advanced Applicationsmentioning
confidence: 99%
See 2 more Smart Citations